Harnessing visible light for sustainable biodiesel production with Ni/Si/MgO photocatalyst - Aminul Islam; Teo, Siow Hwa; Md. Tarekul Islam; Alam Hossain Mondal; Hasan Mahmud; Sozib Ahmed; Md Ibrahim; Yap, Taufiq Yun Hin; Abdulkareem-Alsultan G.; Mohd Lokman Hossain; Md. Chanmiya Sheikh; Adiba Islam Rasee; et al. (Elsevier Ltd., 2025)
Sustainable energy sources frequently demonstrate greater reliability and resilience in comparison to conventional energy sources. Biodiesel, with its markedly reduced carbon footprint when compared to petroleum-based diesel fuel, owes this advantage to its production from renewable resources. Heterojunction photocatalysts have gained significant interest due to their immense promise in tackling environmental challenges. In this study, a highly efficient photocatalyst, Ni/Si/MgO, for biodiesel production under visible light irradiation was synthesized using a solid-phase reaction method with silica as the silicon source, along with Ni and MgO. The surface functionality of Ni/Si/MgO was crucial for achieving high efficiency of photocatalytic systems, as evident from XPS. The transesterification reaction on the Ni/Si/MgO photocatalyst proceeds by the formation of SiH and SiOH bonds over the catalyst. The photocatalytic activities of Ni/Si/MgO photocatalysts were higher than those of the Si/MgO nanoparticle when exposed to light. Achieving an optimal yield of 98 %, the biodiesel production was carried out under the following reaction conditions: A catalyst dosage of 2 % by weight was utilized, along with a methanol-to-oil molar ratio of 12:1, and the entire procedure was executed within a duration of 3.5 h. Plasmonic near-fields are speculated to be responsible for the increased transesterification activity along the Ni/Si/MgO interface. In order to carry out the transesterification reaction, electron-hole pairs are generated along the Ni/Si/MgO interface, where plasmonic near-fields are highly concentrated. This study contributes a significant perspective on mechanisms governing the process of efficient plasmonic photocatalysis responsive to visible light. These findings hold the potential to offer valuable guidance in the formulation and design of next-generation, high-performance photocatalysts.